A Comparative Study of the Indian FMCG Industry's Financial Performance and Valuation Dynamics - Parimalam, Elango J.; S., Satheeshkumar (Indian Journal of Research in Capital Markets, 2025)
The main objective of the study was to compare the financial performance of five major fast-moving consumer goods companies, including Britannia, ITC Limited, Hindustan Unilever Limited, Tata Consumer, and Dabur, between the financial years 2020–2021 to 2024–2025. Quantitative information was collected from the official websites of the five companies’ annual financial statements. To assess growth, market perception, and efficiency, the compound annual growth rates of fundamental key ratios, such as Earnings Per Share, Return on Equity (ROE), Dividend Per Share (DPS), Price to Earnings, Book Value, and Price to Book, were computed for this study and compared among the five companies. Distinctive results were obtained from Tata Consumer Products and ITC Limited. The outcomes of ITC Limited demonstrated excellent market perception, profitability, and efficiency and could be suggested. Additionally, it achieved a high ratio of price to book, ROE, and EPS when compared to other selected companies. Conversely, Tata Consumer Products’ DPS increased at the fastest rate (21%), indicating a positive trend in returns. The research enables individual investors to make well-informed choices regarding long-term investments. Additionally, it is advantageous to institutional and mutual fund investors for long-term returns. This study, in contrast to others, helps distinguish between companies that prioritize intrinsic business growth and those that prioritize immediate returns.